Randomized Phase III evaluation of the efficacy and safety of a novel glycopyrrolate oral solution for the management of chronic severe drooling in children with cerebral palsy or other neurologic conditions - Zeller RS; Lee HM; Cavanaugh PF; Davidson J (Dove Medical Press, 2012)
Robert S Zeller1, Hak-Myung Lee2, Paul Cavanaugh2, Jennifer Davidson21Blue Bird Circle Clinic for Pediatric Neurology at Texas Children's Hospital and Baylor College of Medicine, Houston, TX, USA; 2Shionogi Inc, Florham Park, NJ, USAAim: To evaluate the efficacy of glycopyrrolate oral solution (1 mg/5 mL) in managing problem drooling associated with cerebral palsy and other neurologic conditions.Method: Thirty-eight patients aged 3–23 years weighing at least 27 lb (12.2 kg) with severe drooling (clothing damp 5–7 days/week) were randomized to glycopyrrolate (n = 20), 0.02–0.1 mg/kg three times a day, or matching placebo (n = 18). Primary efficacy endpoint was responder rate, defined as percentage showing ≥3-point change on the modified Teacher's Drooling Scale (mTDS).Results: Responder rate was significantly higher for the glycopyrrolate (14/19; 73.7%) than for the placebo (3/17; 17.6%) group (P = 0.0011), with improvements starting 2 weeks after treatment initiation. Mean improvements in mTDS at week 8 were significantly greater in the glycopyrrolate than in the placebo group (3.94 ± 1.95 vs 0.71 ± 2.14 points; P < 0.0001). In addition, 84% of physicians and 100% of parents/caregivers regarded glycopyrrolate as worthwhile compared with 41% and 56%, respectively, for placebo (P ≤ 0.014). Most frequently reported treatment-emergent adverse events (glycopyrrolate vs placebo) were dry mouth, constipation, and vomiting.Interpretation: Children aged 3–16 years with problem drooling due to neurologic conditions showed a significantly better response, as assessed by mTDS, to glycopyrrolate than to placebo.ClinicalTrials.gov identifier: NCT00425087.Keywords: sialorrhea, randomized controlled trial, cholinergic antagonists